Adventure activities in the educational field: methodological alternatives for Physical Education classes (Research, Society and Development, 2020)
Objective: This article aims to present models of teaching adventure activities in the context of Physical Education (PE) classes. Methods: The research method used was the bibliographic, through exploratory dynamics, plus the use of the observation technique to collect empirical data. Results: Initially, in the first part of the research, we highlighted the centrality of sport from the literary review that refers to the 1980s, a period marked by the numerous contingents of theoretical publications on school PE. Then, in the second section of the study, we discussed about adventure activities in conceptual, analytical and terminological terms. Finally, in the last section of the study, we presented teaching models on adventure activities based on the experiences acquired with the extension project “Escola de Aventuras”, from the Leisure Studies Group (GEL). Conclusion: Through the investigation carried out here, we found that adventure activities can be implemented in the context of school Physical Education content, being an enriching alternative to the traditional activities experienced within the discipline. In this sense, teachers can and should be encouraged to mobilize this content in class, as these activities have a good reception from students.